Trends and correlation of antibiotic susceptibility and antibiotic consumption at a large teaching hospital in China (2007–2016): a surveillance study - Wang R; Yang Q; Zhang S; Hong Y; Zhang M; Jiang S (Dove Medical Press, 2019)
Rongrong Wang,1,* Qing Yang,2,* Shaojun Zhang,1 Yun Hong,1 MeiHua Zhang,1 Saiping Jiang11Department of Pharmacy, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 2Department of Clinical Laboratory, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, People’s Republic of ChinaCorrespondence: Saiping Jiang; MeiHua ZhangDepartment of Pharmacy, The First Affiliated Hospital, College of Medicine, Zhejiang University,  No 79, Qingchun Road, Hangzhou 310003, People’s Republic of ChinaFax +86 571 8723 3411Email j5145@zju.edu.cn meihua_zhang@hotmail.com*These authors contributed equally to this workPurpose: To evaluate the trends and correlation between the antibiotic consumption and susceptibility of eight most frequent isolates in the First Affiliated Hospital of Zhejiang University (2007–2016).Method: This study was based on the yearly surveillance data in a 2500-bed capacity tertiary-care teaching hospital. Trends and correlation were, respectively, analyzed by linear regression and Pearson’s correlation coefficient.Results: The consumption of all antibiotics decreased by 10.8% over time, especially first-generation cephalosporins (p=0.001), fourth-generation cephalosporins (p=0.01), aminoglycosides (p<0.001), and fluoroquinolones (p<0.001), but increased remarkably in linezolid, carbapenems, glycopeptides, and third-generationcephalosporins (3GCs). 72.7% of trend analyses indicated increased susceptibility to antibiotics with remarkably decreased consumption. In particular, susceptibility to aminoglycosides and fluoroquinolones remarkably increased in seven of eight pathogens and negatively correlated with the corresponding antibiotic consumption (p<0.05). Isolation density significantly declined in methicillin-resistant Staphylococcus aureus (54.9–41.3%, p=0.009) and in extended-spectrum β-lactamase producing Klebsiella pneumoniae (42.4–15.6%, p=0.007), which positively correlated with the consumption of fluoroquinolones. The susceptibility to antibiotics with increased consumption was almost stable. Decreased trends were only found in K. pneumoniae to imipenem (81–71.3%, p=0.046) and cefoperazone/sulbactam (70.8–61.0%, p=0.014) and in Acinetobacter baumannii to cefoperazone/sulbactam (59–28%, p=0.007), which negatively correlated with the consumption of carbapenems (r=−0.649, p=0.042) and 3GCs/β-lactamase inhibitors (p<0.05), respectively. The consumption of glycopeptides even positively correlated with the growing susceptibility to vancomycin in Enterococcus faecium (r=0.633, p=0.049) and Enterococcus faecalis (r=0.752, p=0.012).Conclusion: The susceptibility to antibiotics with decreased consumption increased remarkably, but maintained stable to those with growing consumption. The stricter management of carbapenems and 3GCs is necessary.Keywords: antibiotic susceptibility, antibiotic consumption, surveillance, correlation, People’s Republic of China